Crack propagation mechanism and life prediction for very-high-cycle fatigue of a structural steel in different environmental medias - Guian Qian; Chengen Zhou; Youshi Hong (Fracture and Structural Integrity)
The influence of environmental medias on crack propagation of a structural steel at high and very-high-cycle fatigue (VHCF) regimes is investigated based on the fatigue tests performed in air, water and 3.5% NaCl aqueous solution. Crack propagation mechanisms due to different crack driving forces are investigated in terms of fracture mechanics. A model is proposed to study the relationship between fatigue life, applied stress and material property in different environmental medias, which reflects the variation of fatigue life with the applied stress, grain size, inclusion size and material yield stress in high cycle and VHCF regimes. The model prediction is in good agreement with experimental observations.